Acinar cell carcinoma of the pancreas: is resection justified even in limited metastatic disease? - Hartwig, Werner; Denneberg, Maike; Bergmann, Frank; Hackert, Thilo; Hinz, Ulf; Strobel, Oliver; Büchler, Markus W.; Werner, Jens (The American journal of surgery, 2011)
Background - Acinar cell carcinoma (ACC) of the pancreas is characterized by better long-term survival compared with the more common ductal adenocarcinoma, and prognosis is better in resected compared with nonresected patients. The aim of the present study was to investigate the role of surgery in ACC with limited metastatic disease. - Methods - All patients with histologically confirmed ACC treated at the investigators' institution between October 2001 and September 2009 were identified from a prospective database. Clinicopathologic details, perioperative results, and follow-up results were analyzed. - Results - Seventeen patients with nonmetastatic and metastatic ACC were identified. Initially, localized, locoregional, and metastatic disease was present in 5, 7, and 5 patients, respectively. Pancreatic resections were performed in 15 patients. In limited metastatic disease, additional liver resection was performed in 3 patients and omentectomy in 1 patient. In 2 patients, metachronous liver metastases were resected. With a median follow-up period of 36.5 months, overall 1-year, 2-year, and 3-year survival rates were 88%, 65%, and 47%, respectively. Survival of resected patients with metastatic and nonmetastatic disease showed no differences between the 2 groups. - Conclusions - ACC of the pancreas is a relatively rare tumor entity for which resection may result in long-term survival even in limited metastatic disease.
Gesehen am 08.07.2022